Implementasi Kurikulum Merdeka Di TK Al-Mukhlis Tarogong Kaler Garut - Aliyah, Siti; Amalia, Lutvia (LP2M STAI Al-Musaddadiyah Garut, 2024)
The Backround research was motivated by conducting initial observations on March 6 2024 at the TK Al-Mukhlis. TK Al-Mukhlis has one of Sekolah Penggerak batch III. TK Al-Mukhlis has implemented the independent curriculum at the beginning of 2023. The aim of this research is to describe the implementation of the independent curriculum at Al-Mukhlis Tarogong Kaler Garut Kindergarten, to describe the obstacles and challenges faced at Al-Mukhlis Tarogong Kaler Garut Kindergarten in implementing the independent curriculum. The type of research method used in this research is descriptive qualitative research which describes the events encountered. The data collection used is interviews, observation, documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of research at the Al-Mukhlis Tarogong Kaler Garut Kindergarten have implemented an independent curriculum using 5 steps, namely, developing characteristics, developing a vision, mission and goals, planning TP, ATP, assessment, organizing, planning a mentoring system, evaluation and professional development. , the obstacles and challenges faced, teachers have difficulty looking for references to determine teaching modules, the short training time of only 2 weeks online is a new challenge for teachers. Keywords: Early Childhood; implementation; kurikulum merdeka